MANAJEMEN PENINGKATAN MUTU BERBASIS PONDOK PESANTREN - Suwadji, Bpk (e-Journal STAI Muhammadiyah Tulungagung, 2014)
Islamic Boarding School has long been an institution that has an important contribution in educating the nation participating, the number of its students and their schools to make these institutions viable counts in relation to the development of the nation in education and moral. Improvements are continually made to the schools, both in terms of management, academic (curriculum) and facilities, make schools out of the traditional and old-fashioned impression that as long as the bears, it is expected that further changes problematikan boarding able to answer and challenges in the global era here you are.